On the importance of habitat continuity for delimiting biogeographic regions and shaping richness gradients. (7th February 2019) - Fenberg, Phillip B.; Rivadeneira, Marcelo M.
Abstract: The formation and maintenance of biogeographic regions and the latitudinal gradient of species richness are thought to be influenced, in part, by the spatial distribution of physical habitat (habitat continuity). But the importance of habitat continuity in relation to other variables for shaping richness gradients and delimiting biogeographic regions has not been well established. Here, we show that habitat continuity is a top predictor of biogeographic structure and the richness gradient of eastern Pacific rocky shore gastropods (spanning c . 23 000 km, from 43°S to 48°N). Rocky shore habitat continuity is generally low within tropical/subtropical regions (compared to extratropical regions), but particularly at biogeographic boundaries where steep richness gradients occur. Regions of high rocky shore habitat continuity are located towards the centres of biogeographic regions where species turnover tends to be relatively low. Our study highlights the importance of habitat continuity to help explain patterns and processes shaping the biogeographic organisation of species.